Estimation of the biomass yield and stoichiometric coefficient during bioproduct formation through thermodynamic approach: a case study of biosurfactant production. Issue 1 (April 2021) - Adiandri, R S; Purwadi, R; Hoerudin,; Setiadi, T
Abstract: Microbial growth occurs on a wide variety of compounds. One of the critical parameters in biotechnological processes is biomass yield. Biomass yield for many different microbial systems extensively studied due to its primary importance. Besides biomass yield, a stoichiometric coefficient determination is also important because it can predict the number of reactants and products needed. This paper aims to explain how to determine the biomass yield on electron donor (YDX ) and stoichiometric coefficient during bioproducts formation through a thermodynamic approach. The case study focused on the biosurfactant production process. The calculation shows that the electron donor and incubation temperature affect the electron donor's biomass yield (YDX ). For biosurfactant production, glucose obtains a higher value of YDX than propionate. By using the same electron donor, the higher the incubation temperature, the lower of YDX value. YDX value is useful for determining the stoichiometric coefficient of biomass growth during biosurfactants formation through elemental mass balance. The type of electron donor and temperature affect the stoichiometric coefficient of biomass growth during the biosurfactant production process.